CGIAR GENDER Platform Research Agenda: Summary notes of virtual workshop on July 13, 14 & 16, 2020. - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
The GENDER Platform team organized this virtual workshop to move forward the Platform’s research agenda. The workshop was designed to assess and create a shared view of the current state of the gender research portfolio within the Platform and across the centers with an emphasis on multi-center work. One of our key objectives was to evaluate and consider how our portfolio fits with our priorities and consider how we want to build this portfolio going forward. We also set out to better identify core foci of the Platform’s research agenda and, if possible, provide a first draft. As we went into the workshop, we acknowledged that this would be a first step in a longer process. Our next steps will include reaching out and seeking feedback from our key stakeholders and then refine our research path forward and into One CGIAR. The workshop relied on the active and dynamic participation of the Gender Research Coordinators and one additional gender researcher from each center (see Annex 1 for participants). The workshop was facilitated by Nancy White.